Middle Level School Concerns and Rural School-To-Employment Issues: In Search of Better Ways - Conrad F. Toepfer Jr. (Journal of Research in Rural Education, 1997)
Educational planning continues to overlook differences of kind and degree in rural communities. The educational needs specific to young children, young adolescents, and maturing adolescents are likewise often overlooked in school recommendations. The author considers both these concerns in examining the need to help rural youth become employable in today's changing circumstances. The piece focuses upon the needs ofyoung adolescents in rural school/community middle grades programs.